Bioinspired High‐Performance Energetic Materials Using Heme‐Containing Crystals. Issue 29 (5th May 2015) - Slocik, Joseph M.; Drummy, Lawrence F.; Dickerson, Matthew B.; Crouse, Christopher A.; Spowart, Jonathan E.; Naik, Rajesh R.
<x xml:space="preserve">Abstract</x> Synthetic hemozoin crystals (β‐hematin) are assembled with aluminium nanoparticles (nAl) to create a nanomaterial composite that is highly energetic and reactive. The results here demonstrate that hemozoin rapidly oxidizes the nAl fuel to release large amounts of energy (+12.5 ± 2.4 kJ g−1).